Once and for all, LXRα and LXRβ are gatekeepers of the endocrine system. (June 2016) - Maqdasy, Salwan; Trousson, Amalia; Tauveron, Igor; Volle, David H.; Baron, Silvère; Lobaccaro, Jean-Marc A.
Abstract: Liver X receptors (LXRs) α and β are nuclear receptors whose transcriptional activity is regulated by oxysterols, the oxidized forms of cholesterol. Described in the late 1990s as lipid sensors, both LXRs regulate cholesterol and fatty acid homeostasis. Over the years, deep phenotypic analyses of mouse models deficient for LXRα and/or LXRβ have pointed out various other physiological functions including glucose homeostasis, immunology, and neuroprotection. This review enlightens the "endocrine" functions of LXRs; they deeply impact plasma glucose directly and by modulating insulin signaling, renin–angiotensin–aldosterone axis, thyroid and pituitary hormone levels, and bone homeostasis. Besides, LXR signaling is also involved in adrenal physiology, steroid synthesis, and male and female reproduction. Hence, LXRs are definitely involved in the endocrine system and could thus be considered as endocrine receptors, even though oxysterols do not fully correspond to the definition of hormones. Finally, because they are ligand-regulated transcription factors, LXRs are potential pharmacological targets with promising beneficial metabolic effects.